Determinants of Philippine inter-regional migration 1960-1970 - De los Santos, Arlyne G. 1946- (Manila Population Institute, University of the Philippines Manila, 1980)
In this study, some determinants of inter-regional migration in the Philippines were examined through regression analysis. The factors
considered were: regional income differentials, income at
origin,unemployment rates at origin and destination, population density of origin and destination, past migration from region I to region j, past
migration from region j to region I, and distance between origin and destination. By using step-wise regression analysis, those factors that did not significantly contribute to the variation in the inter-regional migration rates of the different groups of migrants were eliminated. This yielded optimal prediction equations for the young, middle-aged, and elderly male migrants; and female counterparts.
The main findings are as follows. All the factors considered explain from more than 62 to over 95 per cent of the variation in the inter-regional migration rates of all the groups of migrants. The explanatory power of the model diminished with age. The propensity to migrate, likewise, diminished with age. So did the influence of the selected factors on inter-regional migration. Young migrants had greater sensitivity to the socio-economic factors than older migrants.
All the factors affected the migration rates of young male and female migrants in the expected direction. For the middle-aged male and female migrants, all the factors affected their migration rates in the expected directions but the effects were very much smaller, although still considerable. Even smaller are the effects of the same factors on the migration rates of elderly male and female migrants, as well as the variation in their migration rates explained.
The findings of this study are not generally contrary to those found in other
countries such as the United States. Like their American counterparts, Filipino migrants in the sixties were young and were strongly influenced by differential economic opportunities like higher income and lower unemployment rates at the destination areas. Filipino male migrants headed for rural areas entailing longer distance moves while female migrants traveled shorter distances, usually toward urban areas. Both cultural groups have been influenced by the presence of relatives and friends in the destination areas. A striking difference though is that American migrants consider distance a deterrent to migration whereas Filipino migrants favor long distance migration. It is possible that the cost of moving in the Philippines is small compared to the United States. After all, the Philippines is small compared to the United States.
The results of the study lend support to the theory that migrants behave as maximizers of expected utility; that migration is an investment increasing the productivity of human resources. Hence, prospective migrants will move only if their perceived benefits out-weigh their perceived costs of moving.
Typescript.
Vita.
Thesis
Keywords: Migration, Internal -- Philippines